The Role of Oxidative Stress as a Mechanism in the Pathogenesis of Acute Heart Failure in Acute Kidney Injury - Danijela Tasić; Zorica Dimitrijević (Diagnostics)
Despite a large amount of research on synchronous and mutually induced kidney and heart damage, the basis of the disease is still not fully clarified. Healthy mitochondria are essential for normal kidney and heart function. Mitochondrial dysfunction occurs when the clearance or process of generation and fragmentation of mitochondria is disturbed. The kidney is the second organ after the heart in terms of the number of mitochondria. Kidney tubules are rich in mitochondria due to the high energy requirements for absorption of large amounts of ultrafiltrate and dissolved substances. The place of action of oxidative stress is the influence on the balance in the production and breakdown of the mitochondrial reactive oxygen species. A more precise determination of the place and role of key factors that play a role in the onset of the disease is necessary for understanding the nature of the onset of the disease and the creation of therapy in the future. This underscores the urgent need for further research. The narrative review integrates results found in previously performed studies that have evaluated oxidative stress participation in cardiorenal syndrome type 3.